Ekstrak metanol batang pisang mauli (Musa sp.) dosis 125-1000 mg/kg bb tidak menimbulkan efek toksik pada hati mencit (Mus musculus) Mauli methanol extract of banana (Musa sp.) dosages of 125-1000 mg/kg bw is not cause toxic effects on the liver of mice (Mus musculus) - Maharani Laillyza Apriasari; Amy Nindia Carabelly; Ghea Tri Andini (DiscoverSys Inc., 2013)
Musa sp. is one of Kalimantan Selatan original plant that empirically has benefit as herbal medicine for acceleration of wound healing. Banana contain many phytochemicals such us saponin, flavonoid, and tannin which can be used asantibiotic, pain relieving and anti inflamantory. This experiment was aimed to know the toxicity effect of methanolicextract of mauli banana stem inmice livers histopathological. The research is pure experimental study using post testonly with control design. Populations were 25 mices, divided into 5 groups. Group I as negative control group weregiven aquadest, and group II, III, IV, and V were given 125 mg, 250 mg, 500 mg, and 1000 mg methanolic extract ofMauli banana stem. They were given treatment daily as long as 21 days. All of the mice were necropsied at day 22, andthe livers were taken for to examine their histopatological changes. Each liver tissue was processed by paraffin blockembededdand hematoxylin eosin staining method. Histopathological changes were examined based on the present necrosis, degeneration, and megalohepathosit lesions. The results showed light necrosis, degeneration, andmegalohepathosit on the treatment group. The conclusion was methanolic extract of Mauli banana stem dosage 1251000mg/kgbwis not toxic significantly on the liver of mice.